2021
DOI: 10.1093/ofid/ofab466.253
|View full text |Cite
|
Sign up to set email alerts
|

51. Sustained Impact of an Antimicrobial Stewardship (AS) Initiative Targeting Asymptomatic Bacteriuria and Pyuria in the Emergency Department (ED)

Abstract: Background The sustainability of unique AS initiatives are largely unstudied. A multi-faceted initiative to reduce inappropriate treatment of asymptomatic pyuria (ASP) and asymptomatic bacteriuria (ASB) in the ED was implemented at our institution in 2016. A pre-post intervention analysis demonstrated reduction in the inappropriate treatment (tx) of ASP/ASB from 100% to 32% (p< 0.001) following the intervention. The purpose of this present study was to determine the sustained impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…23,24 Notably, we did not make changes to urine test ordering in the EMR or ED urine specimen processing, which previous studies have found to be key drivers of UTI over-diagnosis and ASB treatment. 8,10,22,[25][26][27] Our data also support the need for ongoing education regarding UTI diagnosis because 27% of post-intervention patients received antibiotics for UTI despite ED provider documentation of a clear non-UTI cause for their symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…23,24 Notably, we did not make changes to urine test ordering in the EMR or ED urine specimen processing, which previous studies have found to be key drivers of UTI over-diagnosis and ASB treatment. 8,10,22,[25][26][27] Our data also support the need for ongoing education regarding UTI diagnosis because 27% of post-intervention patients received antibiotics for UTI despite ED provider documentation of a clear non-UTI cause for their symptoms.…”
Section: Discussionsupporting
confidence: 59%